(untitled) (A thousand years of Poland’s presence among the elite of European states, 2026)
Monika Zając opens her address by welcoming the attendees, expressing gratitude to the host, Bogdan Święczkowski, President of the Constitutional Tribunal, and outlining the purpose of the gathering. She highlights the significance of the venue, noting that the Constitutional Tribunal, as a guarantor of Polish sovereignty, serves as a symbolic reference to the importance of Bolesław the Brave's coronation. The conference is intended as an opportunity to reflect on the impact of Poland's first royal coronation on the country's history, as well as on the challenges facing the Polish Republic today, and has brought together distinguished representatives of the academic world. The address concludes with expressions of gratitude to the members of the Scientific Committee and to Professor Gertruda Uścińska, Rector of the Nicolaus Copernicus University in Warsaw, whose patronage of the conference lent it additional academic distinction.